Consider a function $f: (0,1) \to \mathbb R$ defined as the following power series: $$ f(x) = \sum_{k=0}^\infty a_k (1-x)^k. $$ This series has $a_k > 0$ and is assumed to converge point-wise for all $x \in (0,1)$.

My question is:

If $x$ in the above expression is replaced by a complex variable $z$, can it be assured that $\sum_{k=0}^\infty a_k (1-z)^k$ converges for all $z$ with $|z-1|<1$?

Here is my attempt at a proof, but I'm not sure it is correct.

The series for $x \in (0,1)$ is absolutely convergent in $(0,1)$ by the assumptions. That is, $\sum_{k=0}^\infty a_k (1-x)^k = \sum_{k=0}^\infty a_k |1-x|^k$ is finite for all such $x$. Replacing $x$ by any complex $z$ such that $|1-z| = |1-x|$, the resulting $\sum_{k=0}^\infty a_k |1-z|^k$ converges to the same value. This implies that the complex series $\sum_{k=0}^\infty a_k (1-z)^k$ (absolutely) converges. Since this holds for any $x \in (0,1)$, the complex series converges for any $z$ in the disk $|z-1|<1$.

Are all my steps correct? If so, is there any shorter proof? If not, is there a counterexample?


The steps are correct. Perhaps you can simplify notation by considering the series $\Sigma_{k=0}^\infty a_ky^k$. It has a radius of convergence $R$; this means that $\Sigma_{k=0}^\infty a_ky^k$ converges absolutely for $\lvert y \rvert < R$ and diverges for $\lvert y \rvert > R$. You know that it converges for $0 < y < 1$; this is possible only when $1 \le R$. The complex series $\Sigma_{k=0}^\infty a_kz^k$ has the same radius $R$ of convergence as the real series.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.